Classification of Preparations Affecting Varroa in Bees - Shodmonov , A.Sh.; Qirg‘izboyev , M.A.; Shomaxsudov , A.Sh.; Egamberganov , B.Z. (American Journal of Biodiversity, 2025)
This article provides information about the medicinal preparations and active substances that affect Varroa jacobsoni mites, the causative agents of varroatosis in honey bees. It describes the methods and dosages used to apply these substances to bee colonies. The information is based on both Uzbek and international scientific literature.